Ethnicity, class, culture or identity? competing paradigms in Malaysian studies - Shamsul A.B. (Universiti Kebangsaan Malaysia, 1998)
`Malaysian studies' as a field of social scientific study has its roots in `colonial knowledge' which in turn has had European social theory and classificatory schema as its epistemological basis. Hence social analysis of Malaysian society; be it based on the `ethnicity' or `class' or `culture' or `identity' paradigm, has been framed in the same epistemological framework. This essay discusses critically the origin of each of the said paradigms, especially its development from the sphere of `public advocacy' to the realm of `academic analyses', in a historical and longitudinal perspectie from the colonial era to the contemporary period, and in due process highlights not only the co-existence and competing nature of these paradigms but also the major contributors and their contributons within each paradigm.